Assessment of antenatal risk factors for the formation of congenital defects of the development of the urinary system in children - E. V. Sergeeva; A. Nee; T. A. Shumatova; O. G. Bykova; N. G. Prikhodchenko; E. S. Zernova (Медицинский совет, 2022)
Introduction. In the Russian Federation, the number of new cases of congenital malformations and chromosomal abnormalities reported among children from birth to 14 years of age each year is over 1,000 per 100,000 population. Therefore, the urgency of the problem of diagnosis and prevention of congenital malformations does not admit of doubt.Purpose of the study. To study the influence of antenatal risk factors on the formation of the urinary system’s congenital malformations in children.Materials and methods. The study carried out by the “case – control” method. The main group included 126 mothers who gave birth to children with kidney and urinary tract defects, and the control group included 40 women with healthy children. The assessment of the results reliability the obtained carried out by calculating the odds ratio with a 95% confidence interval.Results. The most significant factors in the formation of malformations of the urinary system were: the age of mothers over 35 years old (OR 3.264, 95% CI: 1.079–9.875), a burdened obstetric history (OR 2.380, 95% CI: 1.012–5.594), a burdened gynecological anamnesis (OR 2.825, 95% CI: 1.319–6.051), preeclampsia (OR 2.910, 95% CI: 1.057–8.010), exacerbation of opportunistic infections during pregnancy (OR 2.833, 95% CI: 1.103–7.280), the presence of chronic placental insufficiency (OR 3.413, 95% CI: 1.405–8.290), passive smoking during pregnancy (OR 2.711, 95% CI: 1.110–6.618), a burdened nephrological history in the mother (OR 3.462, 95% CI: 1.148–10.442), the presence of neurocirculatory dystonia (OR 4.703, 95% CI: 1.062–20.822). The work revealed the role of folate metabolism genes polymorphisms in the formation of kidney defects. In addition, a reliable relationship between the development of kidney and urinary tract defects with the absence of pregravid preparation was found, as well as untimely intake of folic acid preparations.Conclusions. The study made it possible to identify the most significant factors of the antenatal period, influencing the development of congenital malformations of the urinary system. The results obtained must be taken into account at the stages of planning pregnancy in an outpatient setting.